Autobiographical writings of Rig-ʼdzin ʼJaʼ-tshon-sñiṅ-po - ʼJaʼ-tshon-sñiṅ-po, Gter-ston, 1585-1656 (ʼJaʼ-tshon-sñiṅ-po, Gter-ston, 1585-1656. Revelations of Rig-ʼdzin ʼJaʼ-tshon-sñiṅ-po series ;, 1979)
Autobiographical reminiscences of a master of the Nyingmapa tradition.